PENGGUNAAN APLIKASI LINE-DICTIONARY UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENGUASAI URUTAN PENULISAN GORESAN HURUF MANDARIN - Dinda Wafiq Azizah; Lily Thamrin; Yoanna Afrimonika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Chinese is one of the most popular languages in the world. Chinese language is famous for its letters which are often called Hanzi. In learning Chinese, apart from how to pronounce it, you also learn how to write it. Therefore, the author uses the Line-Dictionary application to help students learn Hanzi, especially how to write it well. The purpose of the study was to find out how the Line-Dictionary app uses in teaching stroke sequences to students, the effects of using the LineDictionary app in studying stroke sequences, and how students respond to the use of the Line-Dictionary app. Authors use quantitative methods through written tests to collect data, as well as qualitative methods by distributing questionnaires to determine students' responses to the use of the Line-Dictionary app. Based on the resultsof the data analysis, showed that the error rate of writing mandarin letters in students was reduced by 24%. This can be seen in the average pre-test error rate of 68%, while in post-test by 44%. The student's response to the use of the Line-Dictionary app in studying the stroke sequence of Mandarin letters was excellent.